2018
DOI: 10.3390/agronomy8050064
|View full text |Cite
|
Sign up to set email alerts
|

Salt Stress Effects on Avocado (Persea americana Mill.) Plants with and without Seaweed Extract (Ascophyllum nodosum) Application

Abstract: Salinity is one of the major factors limiting avocado yield, primarily due to the high concentration of ions in irrigation water. An experiment was conducted on 2 year old avocado plants (Persea americana Mill.) cv. Hass, grafted onto Duke 7 clonal rootstock growing in pots, to determine the effect of salt stress on growth, as well as physiological and biochemical responses, and the effect of seaweed extract (Ascophyllum nodosum) on salinity stress. Treatments consisted of different types of irrigation water: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(29 citation statements)
references
References 35 publications
(21 reference statements)
0
24
0
1
Order By: Relevance
“…Studies revealed that the application of various forms of ANE improved salinity stress tolerance in Arabidopsis, tomato ( Solanum lycopersicum ), passion fruit ( Passiflora edulis ), and avocado ( Persea americana ) (Jithesh et al, 2012, 2018; Bonomelli et al, 2018; Di Stasio et al, 2018; Jolinda et al, 2018; Shukla et al, 2018a). Rygex ® and Super Fifty ® , both commercial extracts of A. nodosum , boosted the accumulation of minerals, antioxidants, and essential amino acids in tomato fruits grown under salinity stress (Di Stasio et al, 2018).…”
Section: Ane Mitigates Abiotic Stresses In Plantsmentioning
confidence: 99%
“…Studies revealed that the application of various forms of ANE improved salinity stress tolerance in Arabidopsis, tomato ( Solanum lycopersicum ), passion fruit ( Passiflora edulis ), and avocado ( Persea americana ) (Jithesh et al, 2012, 2018; Bonomelli et al, 2018; Di Stasio et al, 2018; Jolinda et al, 2018; Shukla et al, 2018a). Rygex ® and Super Fifty ® , both commercial extracts of A. nodosum , boosted the accumulation of minerals, antioxidants, and essential amino acids in tomato fruits grown under salinity stress (Di Stasio et al, 2018).…”
Section: Ane Mitigates Abiotic Stresses In Plantsmentioning
confidence: 99%
“…Among them, A. nodosum is probably the most common species. Although its biomass has been long used as fertilizer, studies carried out with commercial formulations containing A. nodosum extracts proved that they act as enhancers of growth, yield, quality, and adaptation to stress in salinized lettuce ( Lactuca sativa ), thale cress ( Arabidopsis thaliana) , tomato ( Solanum lycopersicum ), passion fruit ( Passiflora edulis ), and avocado ( Persea americana ) [ 108 , 114 , 116 , 117 , 131 , 132 , 133 , 134 ]. Several studies have been carried out in soil, thus making it difficult to entangle the direct (e.g., nutritional and biostimulatory activities) and indirect (e.g., manurial effect) impact on crops.…”
Section: Mechanisms Of Salinity Stress Tolerance In Macro and Micrmentioning
confidence: 99%
“…Moreover, these amino acids can scavenge ROS through a not fully elucidated mechanism [ 101 , 141 ]. A. nodosum extracts boost RUE in avocado under salinity, enhancing growth and yield [ 117 ]. The extract of this alga helps plants to better discriminate between sodium and potassium, maintaining higher K/Na ratios [ 115 ].…”
Section: Mechanisms Of Salinity Stress Tolerance In Macro and Micrmentioning
confidence: 99%
“…Concentrations of these elements were then determined with an atomic absorption spectrophotometer (EAA Analyst 200, Perkin Elmer, Wellesley, MA, USA) according to the methodology described by the Analytical Association of Official Analytical Chemist (AOAC) [27]. For nutrient content (absolute quantity) determination, concentrations in each organ (%DW) were multiplied by the organ dry weight [28].…”
Section: Treatmentmentioning
confidence: 99%
“…Official Analytical Chemist (AOAC) [27]. For nutrient content (absolute quantity) determination, concentrations in each organ (%DW) were multiplied by the organ dry weight [28].…”
Section: Plant Dry Weight and Nutrient Contentmentioning
confidence: 99%